Current care for victims of sexual violence and future sexual assault care centres in Belgium: the perspective of victims - Laura Peeters; Anke Vandenberghe; Bavo Hendriks; Christine Gilles; Kristien Roelens; Ines Keygnaert (BMC, 2019)
Abstract Background Sexual violence is a global health problem. After ratifying the Convention of Istanbul in 2016, this Belgian study was set up to map the perspective of victims of rape on the current sexual violence care provision in Belgium and to inquire on their need for more specialised and holistic care in future Sexual Assault Care Centres. Methods Sixteen rape victims participated in this sub-study. A mixed-method design (questionnaire, in-depth interview or small focus group) was applied depending on the time elapsed between rape and participation. Descriptive Thematic Framework Analysis was performed in duo. Results The participants thought it of utmost importance that every victim should receive all medical, psychological and forensic care without necessarily having to involve the police first. They stated that the current Belgian sexual violence care provision could be much more patient-centred, specifically the forensic examination and psychological care. Alongside medical and psychological consequences, victims emphasised the high personal financial and relational burden of sexual violence. The holistic care offered in Sexual Assault Care Centres was perceived to enhance the recovery process of victims of sexual violence. Their doors should be open to all victims and their relatives. They should not only provide acute care for the victim, but also improve victims' reintegration into society while reducing their personal costs significantly. Conclusion All care for victims of sexual violence, especially forensic and psychological care, needs drastic improvement in Belgium. All participants agreed that having specialised, multidisciplinary and longitudinal care in a Sexual Assault Care Centre that would be open 24/7 for everyone, victims and their significant others, would be an improvement to the currently available care all over Belgium. Trial registration This research was registered on April 1st 2016. Registration number B670201628242.